Large elastic deflection of a rock plate - Singh J.G.; Upadhyayxx P.C. (My University, 2025)
The thin coal layer left against the weak roof of the underground openings has been simulated as a thin plate of bi-elastic material, undergoing large elastic deflection. An approximate solution of the deflection of a membrane has been superimposed on the deflection obtained by the classical plate theory (after incorporating the double elasticity) to obtain the final deflection equation. The effect of the degree of bi-elasticity is found to be significant. © 1987 Elsevier Science Publishers B.V.